Properties of Nanogenerator Materials for Energy-Harvesting Application - Majid, W.H. Abd.; Ahmad, N.; Rosli, A.K.; Sarjidan, M.A. Mohd; Halim, N.A. (Journal of Research Updates in Polymer Science, 2023)
Advancements in nanotechnology and materials science have led to the development of a variety of nanogenerator materials with improved properties, making energy harvesting technologies increasingly viable for various applications, such as powering wearable devices, remote sensors, and even small electronic gadgets in the future. The evolution of hybrid materials consisting of polymers and nanoparticles as efficient energy harvesters and energy storage devices is in high demand nowadays. Most investigations on organic ferroelectric P(VDF-TrFE) as a polymer host of polymer nanocomposite devices were primally focused on the β phase due to its excellent electrical properties for various application purposes. Nanofiller is also introduced into the polymer host to produce a polymer nanocomposite with enhanced properties. A brief description of various physical quantities related to ferroelectric, dielectric, pyroelectric effects and Thermally Stimulated Current (TSC) for energy harvesting applications in nanogenerator materials is presented. This article explores the different materials and uses of various nanogenerators. It explains the basics of the pyroelectric effect and the structure of pyroelectric nanogenerators (PNGs), as well as recent advancements in micro/nanoscale devices. Additionally, it discusses how the performance of ferroelectric, dielectric, pyroelectric, and TSC are impacted by the annealing treatment of P(VDF-TrFE) polymer.